Clinical management of postpartum hemorrhage: an integrative review (Research, Society and Development, 2021)
Introduction: Postpartum hemorrhage is the cause of approximately 25% of all deaths of pregnant women worldwide and is responsible for a large proportion of severe maternal morbidities. Thus, we aimed to evaluate and synthesize the latest publications on the clinical treatment of this event. Methodology: This is an integrative review conducted from January to June 2021, which aimed to answer the following guiding question: "What is the recent evidence available in the literature on the clinical treatment of postpartum hemorrhage? The search considered the last 5 years and resulted in 150 articles, of which 12 were selected due to eligibility criteria. Results: All articles were randomized clinical trials and written in English, published in international journals. Regarding the countries of performance, 4 studies were performed in two or more countries and the others were performed in 7 different countries. Discussion: Oxytocin infusion is considered the gold standard for the treatment of postpartum hemorrhage. However, when there is unavailability or contraindication to the use of this drug, data on recommendations for second-line therapies are lacking. In this sense, other drugs such as methylergometrine, tranexamic acid, misoprostol, among others, may become advantageous. Conclusion: Due to the impact that this hemorrhage has on maternal health, the importance of identifying secondary strategies for its control is evident, demonstrating the appropriate routes of administration, safety and effectiveness of the drugs.